Pelatihan Pemanfaatan AI Quizlet untuk Mempermudah Guru Membuat Alat Penilaian untuk Peserta Didik - Astutik, Leny Suryaning; Rizqy Ana, Ria Fajrin; Sari, Nadin Nabila (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Based on Government Regulation No. 74 of 2008, the main duties of teachers include teaching, guiding, directing, training, assessing, and evaluating students. One AI platform that can be utilized by teachers and students for assessment is Quizlet. Quizlet is an Artificial Intelligence tool designed to help teachers save time in preparing materials and quizzes as objective, effective, and interactive assessment tools. Problem analysis shows that SDN 3 Panjerejo rarely participates in training, even though its technological infrastructure is adequate. This community service aims to (1) conduct training on creating assessments using Quizlet, (2) provide information about AI platforms that support teachers in the learning process, and (3) improve teachers’ competence in using Quizlet effectively. The method includes preparation, implementation, and evaluation stages. Results show that 98% of respondents found the training very useful, improving teachers’ skills and making assessment creation easier.